2006
DOI: 10.1038/ng1869
|View full text |Cite
|
Sign up to set email alerts
|

Dual feedback loops in the GAL regulon suppress cellular heterogeneity in yeast

Abstract: Transcriptional noise is known to be an important cause of cellular heterogeneity and phenotypic variation. The extent to which molecular interaction networks may have evolved to either filter or exploit transcriptional noise is a much debated question. The yeast genetic network regulating galactose metabolism involves two proteins, Gal3p and Gal80p, that feed back positively and negatively, respectively, on GAL gene expression. Using kinetic modeling and experimental validation, we demonstrate that these feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
95
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 29 publications
7
95
0
Order By: Relevance
“…Characteristics of regulatory networks that confer robustness include pathway redundancy and master regulatory organization (5), phenotypic capacitors (6-8), paired activating and inhibiting inputs (9), and cooperative and feed-forward regulation (10). Additionally, negative regulatory feedback, in which a biomolecule represses its own abundance, can buffer variation in gene expression (11,12), and negative feedback loops have been shown to underlie robustness to variable environmental conditions and stochastic intracellular change (13)(14)(15). Negative feedback may also confer network stability against the effects of mutations (3,16), but evidence for negative feedback as a driver of mutational robustness in vivo has been at a premium (17); the relevance of this principle to natural genetic variation remains largely unknown.…”
mentioning
confidence: 99%
“…Characteristics of regulatory networks that confer robustness include pathway redundancy and master regulatory organization (5), phenotypic capacitors (6-8), paired activating and inhibiting inputs (9), and cooperative and feed-forward regulation (10). Additionally, negative regulatory feedback, in which a biomolecule represses its own abundance, can buffer variation in gene expression (11,12), and negative feedback loops have been shown to underlie robustness to variable environmental conditions and stochastic intracellular change (13)(14)(15). Negative feedback may also confer network stability against the effects of mutations (3,16), but evidence for negative feedback as a driver of mutational robustness in vivo has been at a premium (17); the relevance of this principle to natural genetic variation remains largely unknown.…”
mentioning
confidence: 99%
“…These findings are in agreement with earlier findings on sulphur-source shifts with yeast [48][49][50] . Earlier studies on different nutrient shifts have reported the existence of a subpopulation of cells that does not respond at all 2,3,5,6 or the occurrence of very dispersed response times 4,7,8 across a range of microbial species. In these cases, stochasticity in the cell population is large, mostly due to stochasticity in response times, leading either to a bimodal or very broad distribution of cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Then they have to rely on stochasticity-induced adaptation mechanisms. This applies for instance to E. coli with respect to lactose and for S. cerevisiae in the case of galactose 4,[7][8][9] . In such a case, the organism has to rely on leaky gene expression of dedicated permeases.…”
mentioning
confidence: 99%
See 2 more Smart Citations